Paratracheal air cyst in a foal. (3rd March 2021) - Zetterström, S.; Horzmann, K.; Yin, J.; Moon, R.; Boorman, S.; Ceriotti, S.; Wooldridge, A.; Boone, L.
Summary: A 1‐day‐old American Paint Horse was presented for a large air‐filled mass along the ventral aspect of the neck. Bronchoscopy and oesophagoscopy revealed no sign of communication with the trachea or oesophagus. Radiographs and a computed tomography scan of the neck identified a communicating tract between the lumen of the cystic mass and mid‐trachea. The foal was systemically healthy at this initial presentation, and delayed removal of the cyst was recommended to allow further maturation of the foal prior to undergoing general anaesthesia. Upon discharge, the cyst continued to grow in size and became more fluid than air‐filled requiring repeat centesis and draining. The foal was then re‐presented at 3 weeks of age for surgical removal. In surgery, direct communication with the trachea was identified and ligated. Histopathology demonstrated that the cyst lining was composed of squamous epithelium with goblet cells and occasional ciliated cells. The location, morphological features and congenital presentation of the mass were consistent with a paratracheal air cyst (PAC). Surgical resection resulted in excellent functional and cosmetic outcome. Although not previously reported in horses, PAC should be included in the differential diagnosis of an air‐filled ventral neck mass in equine neonates. Complete surgical excision may result in a successful outcome.